Role of Vitamin D as an Adjuvant to Oral Hypoglycemic Drugs in Treatment of Type-2 Diabetic Patients - Garg, Sughandha; Mallik, Debayan (Asian Journal of Medical Sciences, 2020)
Background: Type 2 diabetes mellitus (T2DM) is considered as one of the nonskeletal diseases related with deficiency of vitamin D. Both T2DM and vitamin D deficiency have similar risk factors, such as obesity, aging, and sedentary lifestyle. Cardiovascular diseases (CVDs) and metabolic syndrome disorders are also associated with vitamin D deficiency. Vitamin D plays an important functional role in glucose homeostasis through its effects on insulin secretion and sensitivity. It may reduce insulin resistance (IR) indirectly through its effect on calcium and phosphate metabolism and through upregulation of the insulin receptor gene. Thus, this study was designed to evaluate role of vitamin D as an adjuvant to oral hypoglycemic drugs in treatment of Type 2 diabetic patients. Aims and Objectives : Vitamin D deficiency appears to be related to the development of diabetes mellitus type 2 and the metabolic syndrome. Vitamin D may affect glucose homeostasis, vitamin D levels having been found to be inversely related to glycosylated hemoglobin levels in diabetes mellitus. The aim of the study was to evaluate role of vitamin D as an adjuvant to oral hypoglycemic drugs in treatment of Type 2 diabetic patients. Materials and Methods: The study was done on 60 patients diagnosed with T2DM. A total of 60 patients, control group were type 2 Diabetic patients on oral hypoglycemic drugs without vitamin D supplementation (n=30) and study group was type 2 Diabetic patients on oral hypoglycemic drugs with vitamin D supplementation (n=30). Results: The mean aged of patients was 43.27±8.80 in control group and 47.93±8.39 in study group. The family history of diabetes mellitus was 39 patients. HbA1C, FBG, Postprandial were decreased in study group as compared to control group from baseline (0 day) to 90 days, respectively. Other parameters like hemoglobin, Serum Creatinine serum glutamic oxaloacetic transaminase and serum glutamic pyruvic transaminase were slight changes in study group as compared to control group from baseline (0 day) to 90 days, respectively. Conclusion: The present study demonstrated that vitamin D as an adjuvant to oral hypoglycemic drugs in treatment in diabetic patients, vitamin D levels being related to glycemic control in diabetes mellitus type 2. These findings may have therapeutic implications as cautious vitamin D supplementation may improve glycemic control in diabetes mellitus type 2.